Development of Floss Made From Local Food In Mamboro Village: Pengembangan Abon Berbahan Dasar Pangan Lokal Di Kelurahan Mamboro - Ansar Ansar; Rusli Maudu; Nuning Sri Febriyanti (Poltekkes Kemenkes Palu, 2021)
Food diversification connotes the selection of alternative food ingredients to reduce dependence on one dominant type of food. So far, the dominant type of food in Indonesia is rice. Therefore, food diversification is one of the strategies to achieve food security. Floss is a food that is generally made from beef. beef floss is often found, but combining products from one food ingredient with other foodstuffs is still rarely found. Combining several food ingredients will increase the nutritional value of a food product. Organoleptic test design for storability and acceptability of Shredded-Based Local Food with a panel of 25 students. The data is presented in tabular form accompanied by an explanation of the table in the form of narration. Abon made from local food is acceptable in terms of taste, color, texture and aroma.